The Influence Of Work Environment And Career Development On Employee Performance At PT. PLN Nusantara Power Umro Uphk Medan - Noor, Nadya; Nasution, Muhammad Amri; Firah, Al (Universitas Dharmawangsa Medan, 2025)
This study aims to determine the effect of work environment and career development on employee performance at PT. PLN Nusantara Power UMRO UPHK Medan. The research method used quantitative data. The results of this study indicate that the significant value of the work environment variable (X1) is smaller than the probability value of 0.05, or a value of 0.000 <0.05, then Ha is accepted H0 is rejected. Variable X1 has a tcount value (8.186) greater than ttable (1.9869). So it can be concluded that the work environment partially has an influence and is significant on employee performance. The significant value of the career development variable (X2) is smaller than the probability value of 0.05, or a value of 0.000 <0.05, then Ha is accepted H0 is rejected. Variable X2 has a tcount value (8.306) greater than ttable (1.9869). So it can be concluded that career development partially has an influence and is significant on employee performance. Fcount value = 146.393 > Ftable 3.10 with a significance value of 0.001 smaller than 0.05. So it can be concluded that simultaneously the work environment and career development affect employee performance at PT. PLN Nusantara Power UMRO UPHK Medan. The R Square value has a value of 0.767. Thus, the contribution of the current ratio of the work environment (X1) and career development (X2) to profitability is 76.7% and the remaining 23.3% is influenced by other independent factors or variables.